'Do horses cause divorces?' Autoethnographic insights on family, relationships and resource-intensive leisure. Issue 3 (26th May 2020) - Dashper, Katherine; Abbott, Julie; Wallace, Carrianne
ABSTRACT: Equestrian leisure is resource-intensive and requires significant investment of time, money, effort and emotion. In this paper we consider these demands within the context of personal and family relationships. Using autoethnographic methods we use our own relationships with horses and with our human partners to explore the issues and tensions than can arise when one person engages in such an intense and demanding leisure pursuit. We argue that support from partners is essential, but may often be underpinned by some resentment towards the horse(s) and the commitment they entail. Framed within the context of gendered family relationships and gendered leisure, we suggest that women's involvement in resource-hungry leisure, such as equestrianism, is filtered through traditional gender power relations and that constant negotiation and compromise is required to enable women to engage in demanding leisure activities.